The effectiveness of teaching the theory of TRIZ in expressive performance and the development of creative thinking among preparatory school students (Journal of the College of Education for Women, 2019)
The current research aims to find out (the effectiveness of teaching TRIZ theory in the expressive performance and the development of creative thinking among preparatory school students)To achieve this, the researcher adopted on an experimental design is located in women with partial seizure experimental designs field in order to achieve the goals of the research, has sample consisted of two divisions seminars Mentzmtin in junior high school Diyala for Boys, and divided the sample of (60) called on the two groups, the first pilot of ( 30) student, and the other officer and number (30), student, and studied researchers experimental group theory TRIZ, while he studied the officer in the traditional manner, the researcher conducted a parity statistically between the two groups of research in a number of variables, namely, (chronological age measured in months, and the educational attainment of the parents, and the IQ test and the degrees of the pre-test creative thinking, and degrees of pre-test performance